Human Resources in the Social Services – Problems and Challenges in the Bulgarian Regions - Lyubomirova, Veselina; Nikolov, Georgi (Research Papers, 2021)
The research reveals current work motivation challenges and employment problems in the social care system in Bulgaria. On that basis, are outlined some challenges for the social care system in the Bulgarian regions. The conclusions are based on the authors’ survey data and a content analysis of the social services strategies in 22 Bulgarian NUTS 3 regions (districts). The paper shows which ongoing problems in the sector demotivate the social work specialists due to their own opinions and are not solved as policy and planning in the regional and municipality strategies and government level.